2018
DOI: 10.1002/iub.1750
|View full text |Cite
|
Sign up to set email alerts
|

L‐rhamnose induces browning in 3T3‐L1 white adipocytes and activates HIB1B brown adipocytes

Abstract: Induction of the brown adipocyte-like phenotype in white adipocytes (browning) is considered as a novel strategy to fight obesity due to the ability of brown adipocytes to increase energy expenditure. Here, we report that L-rhamnose induced browning by elevating expression levels of beige-specific marker genes, including Cd137, Cited1, Tbx1, Prdm16, Tmem26, and Ucp1, in 3T3-L1 adipocytes. Moreover, L-rhamnose markedly elevated expression levels of proteins involved in thermogenesis both in 3T3-L1 white and HIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Although rosiglitazone has been reported to have browning effects during the adipocyte by activating MAPK and PI3K signalling pathways [38], it has also been extensively reported as an enhancer of white adipocyte full differentiation since it triggers peroxisome proliferator activator receptor gamma (PPARγ) overexpression, the master regulator of both BAT and WAT adipogenesis [39,40]. Adding factors that target β-adrenergic stimulation, such as L-rhamnose, T3, irisin, fibroblast growth factor 21, or follistatin to the previous cocktail have been described to induce fat browning [32,[41][42][43][44]. Protocol 1 which consisted in T3 treatment, in addition to the basal cocktail for white adipocyte differentiation, showed to be the most successful in inducing beige phenotype mainly because this thyroid hormone potentiates the effects of the β-adrenergic receptors in glucose metabolism and increases the thermogenic capacity of adipose tissue to enhance energy expenditure [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rosiglitazone has been reported to have browning effects during the adipocyte by activating MAPK and PI3K signalling pathways [38], it has also been extensively reported as an enhancer of white adipocyte full differentiation since it triggers peroxisome proliferator activator receptor gamma (PPARγ) overexpression, the master regulator of both BAT and WAT adipogenesis [39,40]. Adding factors that target β-adrenergic stimulation, such as L-rhamnose, T3, irisin, fibroblast growth factor 21, or follistatin to the previous cocktail have been described to induce fat browning [32,[41][42][43][44]. Protocol 1 which consisted in T3 treatment, in addition to the basal cocktail for white adipocyte differentiation, showed to be the most successful in inducing beige phenotype mainly because this thyroid hormone potentiates the effects of the β-adrenergic receptors in glucose metabolism and increases the thermogenic capacity of adipose tissue to enhance energy expenditure [45].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were treated with 10 µM isoproterenol for 4 h before harvest. For the second protocol (protocol 2), adapted from [42], beige differentiation was induced by 0.25 µM dexamethasone, 0.5 mM IBMX, 10 µg/mL insulin, and 100 µM L-rhamnose (Sigma-Aldrich, St. Louis, MO, USA) in CM for seven days. For the third protocol (protocol 3), adapted from [49], cells were treated with 0.5 µM rosiglitazone, 0.5 mM IBMX, 2 µg/mL dexamethasone, 125 µM salicylate, 5 µg/mL insulin, and 1 µM T3 in CM for two days.…”
Section: T3-l1 Cell Culture and Treatmentsmentioning
confidence: 99%
“…IGF1 stimulates both the proliferation and differentiation of pre-adipocytes in cell culture ( Duffield et al, 2008 ). Furthermore, CITED1 gene promotes cell proliferation and migration, and it is also a marker gene when browning of white adipocytes was induced ( Choi et al, 2018 ; Xia et al, 2018 ). In addition, SLC22A4 was differentially expressed between STHS and TS, and SLC27A6 was identified as a candidate gene in tail fat development ( Kang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SNS induces the release of cathecolamines like norepinephrine, which, through binding to β 3AR, trigger PKA and p38 activation and promote UCP1 transcription partly via p38-mediated modulation of ATF2 and PGC1 α transcriptional activity ( 129 ) ( Figure 4 ). UCP1 expression is also activated via β 3AR-stimulated p38 activation by a series of naturally occurring compounds, such as thymol ( 130 ), cinnamaldehyde ( 131 ), L-rhamnose ( 132 ), grape pomace extract ( 133 ), and mangiferin ( 134 ). Along with β 3AR pathway induction, cold-induced WAT browning is also mediated by stimulation of the histamine H4 receptor, which acts through intracellular calcium mobilization and p38 and ERK activation, promoting PGC1 α and UCP1 expression ( 135 ).…”
Section: P38 and White Adipose Tissue Browningmentioning
confidence: 99%
“…This assumption based largely on data from cell culture studies using p38 α inhibitors, which blunt stimulation of the thermogenic program. However, non-specific effects of these inhibitors cannot be excluded, and several studies have shown that these inhibitors reduce p38 phosphorylation, revealing inhibition of upstream kinases, which in some cases might result in hyperactivation of other p38 isoforms ( 86 , 102 , 130 , 132 , 133 , 151 , 170 ). Despite these concerns about inhibitor specificity, studies with p38 α genetic mutant mice were not reported until recently.…”
Section: P38 and White Adipose Tissue Browningmentioning
confidence: 99%